(untitled) (Research, Society and Development, 2022)
Aging is an inevitable process, with this, several biological, psychosocial and cultural changes occur in the elderly. However, there are still several aspects of aging that need to be reinforced in society, such as the sexuality of the elderly. In view of the above, guiding questions arise: What care for the sexuality of the elderly would be offered and effective? Thus, the objective of this work is to understand the state of the art of studies on the sexuality of the elderly. Object of study: Perception of sexuality in the elderly. The specific objectives are: to identify studies on the sexuality of the elderly; establish thematic categories based on the findings. The research was based on an integrative literature review in the VHL Nursing database, gathering articles that met the criteria. Result: quantitative, production per year and type of methods used, leading to the emergence of two thematic categories from the findings: Category 1: Perception and Distortion on the sexuality of the Elderly and Category 2: Health and sexuality education. The results show the need for public policies aimed at health education to circumvent the distortions about the sexuality of the elderly by the elderly themselves, their family and society as a whole, as well as avoid other problems such as sexually transmitted diseases. It concludes with the importance of the nursing team for awareness, affective care and attentive listening to the elderly, seeking to clarify the changes in the aging process and the possibility of experiencing sexuality in different ways, in order to raise awareness of the elderly, families and the whole of society through assistance.